Removal of Pb(II) Ions from Contaminated Water by Polymer-Supported Ultrafiltration - L.Yu. Yurlova; A.P. Kryvoruchko (Adsorption Science & Technology)
Through the ultrafiltration of water containing Pb(II) ions and poly(ethyleneimine) as an example, it was possible to determine the Pb(II) ion retention coefficients by UPM-20 membranes and the corresponding transmembrane fluxes. The optimal parameters, i.e. pH and concentration ratio C Pb(II) /C PEI , necessary to remove Pb(II) ions from aqueous media using a complexation/ultrafiltration technique (polymer-supported ultrafiltration) were also determined. The state of water in the membranes and its quantity were found using differential scanning calorimetric methods. On the basis of investigations by the method of differential scanning calorimetry, it was possible to assume that the layers of Pb(II)-poly(ethyleneimine) complexes and Pb(II) hydroxo complexes were situated either on the membrane surface or in its pores. In addition, a relationship was established between the transmembrane transfer of Pb(II) ions and the amount of free and bound water in the membrane under investigation.